(untitled) (Web of Teachers: Inderscience Research, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide. Numerous studies have demonstrated that lifestyle factors play a crucial role in both the development and prevention of these conditions. This study aims to evaluate the influence of physical activity, diet, smoking, and stress management on the prevention of cardiovascular diseases. A cross-sectional study was conducted among 500 adult participants aged 30–65 years. Data were collected using standardized questionnaires and clinical measurements. The results indicate that regular physical activity, a balanced diet, and avoidance of smoking significantly reduce the risk of CVDs. These findings highlight the importance of lifestyle modification as a primary preventive strategy against cardiovascular diseases.